2014
DOI: 10.1177/0961203314538332
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to phosphatidylserine/prothrombin complex and the antiphospholipid syndrome

Abstract: Antibodies to prothrombin can be detected by ELISA using prothrombin coated onto irradiated plates (aPT) or the phosphatidylserine/prothrombin complex as antigen (aPS/PT) and they have been both related with the clinical manifestation of APS. Current evidence supports the concept that they belong to distinct populations of autoantibodies. Nevertheless, they can both be detected simultaneously in one patient.This mini-review will focus on data available on aPS/PT antibodies and their clinical utility in the dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Specifically, some IgG aPS/PT require a significant structural reorganization of the antigen for proper recognition in solution, whereas IgG aPT-A target epitopes that are constitutively exposed to the solvent in both closed and open forms of prothrombin. [37][38][39] Given that IgG aPS/PT, and not IgG aPT-A, significantly correlate with thrombosis and obstetric complications, 13,14,20 these findings also raise the interesting hypothesis that excessive stabilization of the open form of prothrombin in vivo may contribute to the onset and progression of APS. Second, we discovered that IgG aPS/PT are heterogeneous, and APS patients positive for IgG aPS/PT can be classified into 2 groups (group A and group B) according to their autoantibody profile.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Specifically, some IgG aPS/PT require a significant structural reorganization of the antigen for proper recognition in solution, whereas IgG aPT-A target epitopes that are constitutively exposed to the solvent in both closed and open forms of prothrombin. [37][38][39] Given that IgG aPS/PT, and not IgG aPT-A, significantly correlate with thrombosis and obstetric complications, 13,14,20 these findings also raise the interesting hypothesis that excessive stabilization of the open form of prothrombin in vivo may contribute to the onset and progression of APS. Second, we discovered that IgG aPS/PT are heterogeneous, and APS patients positive for IgG aPS/PT can be classified into 2 groups (group A and group B) according to their autoantibody profile.…”
Section: Discussionmentioning
confidence: 97%
“…[12][13][14][15] Using enzyme-linked immunosorbent assays (ELISA), aPS/PT have been found primarily in 2 types of APS patients: (1) patients positive solely for lupus anticoagulant 13,[16][17][18] (as discussed in Table 1 of the review by Amengual et al 19 ); and (2) patients positive for lupus anticoagulant, anti-cardiolipin (aCL), and anti-b 2 -glycoprotein I (anti-b 2 GPI) antibodies who carry the highest risk of thrombosis and recurrence, the so-called "triple-positive." 12,14,20 Because of these clinical observations and earlier research conducted in animal models of APS-induced thrombosis, [21][22][23] it has been hypothesized that aPS/ PT may be responsible for some of the vascular and obstetric manifestations observed in patients with APS; testing for aPS/PT could therefore be requested by physicians to confirm or reinforce an APS diagnosis in selected patients or even adopted as a new test to identify novel APS patients at higher risk of thrombosis who would otherwise go undetected with the use of current testing methods.…”
Section: Introductionmentioning
confidence: 99%
“…While the diagnostic utility of these antibodies is in evolution, there are numerous studies on their association with thrombosis or antiphospholipid antibody syndrome, or both. 2,3 Most recently, a systematic review (N = 7,000) concluded that prothrombin antibodies (aPT, aPS/PT) were strong risk factors for thrombosis (odds ratio 2.3, 95% confi dence interval 1.72-3.5). 4 The revised Sapporo (Sydney) guidelines referenced by the authors addressed these "non-criteria" antiphospholipid antibodies.…”
Section: To the Editormentioning
confidence: 99%
“…phosphatidylinositol, phosphatidylserine) while others react with phospholipid binding proteins (e.g. distinct domains of β2GP1, prothrombin, annexin-V) [17][18][19] . The pathogenic role of non-criteria aPLs as well as their importance in defining APS phenotypes is yet to be revealed.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, such roles were described for some non-criteria aPLs, for instance antiphosphatidylethanolamine (aPE) and anti-phosphatidylserine (aPS) with recurrent pregnancy losses [17][18][19][20][21] or anti-phosphatidylserine/prothrombin (aPS/PT) with thrombosis 21 . Notably, inconsistencies regarding criteria and non-criteria aPLs have been reported 16 and most studies evaluated a single or a few non-criteria aPLs, frequently using different diagnostic platforms, which may be difficult to compare.…”
Section: Introductionmentioning
confidence: 99%